The Appell function F1 and Regge string scattering amplitudes - Jen-Chi Lee; Yi Yang (Physics Letters B, 2014)
We show that each 26D open bosonic Regge string scattering amplitude (RSSA) can be expressed in terms of one single Appell function F1 in the Regge limit. This result enables us to derive infinite number of recurrence relations among RSSA at arbitrary mass levels, which are conjectured to be related to the known SL(5,C) dynamical symmetry of F1. In addition, we show that these recurrence relations in the Regge limit can be systematically solved so that all RSSA can be expressed in terms of one amplitude. All these results are dual to high energy symmetries of fixed angle string scattering amplitudes discovered previously [4–8].